The Feasibility and Future of Middle-state Hedging - Cheng-Chwee KUIK; Nur Shahadah JAMIL (East Asian Policy)
Hedging, similar to all forms of state alignment behaviour and foreign policy choice, is dynamic and adaptive, rather than static. Hedging emerges and evolves under certain circumstances; and it will end when those conditions diminish. By examining Malaysia’s China policy, this article identifies the factors at the structural, bilateral and domestic levels that collectively determine the feasibility and future of middle-state hedging in contemporary time.